Violent offenders: theory, research, public policy, and practice - DeLisi, Matt (Jones and Bartlett Publishers)
The importance of violent offenders to criminology -- Where I'm from : criminal predators and their environments -- The behavioral genetics of predatory criminal behavior -- The socialization of violent criminal offenders : notes from the theory of differential oppression -- Biosocial dynamics : a transdisciplinary approach to violence and predation -- Early risk factors for homicide offenders and victims -- Generality of deviance and predation : crime-switching and specialization patterns in persistent sexual offenders -- Comparing women and men who kill -- Gang involvement and predatory crime -- Still psychopathic after all these years -- The heterogeneity of predatory behaviors in sexual homicide -- Criminal predatory behavior in the federal bureau of prisons -- Civil commitment laws for sexual predators -- Prosecuting criminal predators -- Institutional misconduct among capital murderers -- Sex offenders on the Internet : cyber-struggles for the protection of children -- Sex offender registries and criminal predators -- Domestic abuse program-generated risks of battered women